NEONATAL VISUAL INFORMATION PROCESSING IN COCAINE-EXPOSED AND NON-EXPOSED INFANTS - Singer, Lynn T. (Infant Behav Dev, 1999)
This study investigated early neonatal visual preferences in 267 poly drug exposed neonates (131 cocaine-exposed and 136 non-cocaine exposed) whose drug exposure was documented through interviews and urine and meconium drug screens. Infants were given four visual recognition memory tasks comparing looking time to familiarized stimuli of lattices and rectangular shapes to novel stimuli of a schematic face and curved hourglass and bull’s eye forms. Cocaine-exposed infants performed more poorly, after consideration of confounding factors, with a relationship of severity of cocaine exposure to lower novelty score found for both self-report and biologic measures of exposure, Findings support theories which link prenatal cocaine exposure to deficits in information processing entailing attentional and arousal organizational systems. Neonatal visual discrimination and attention tasks should be further explored as potentially sensitive behavioral indicators of teratologic effects.